Análise geossistêmica e quantificação de perda de solo da bacia do Rio Mutum-Paraná (RO) - Michel Watanabe; Fabiano Antonio de Oliveira; Dorisvalder Dias Nunes; Tatiane Emilio Checchia (Confins)
The present study aims to assess the soil loss due erosion from Mutum-Parana river watershed in Rondonia, in order to contribute for a better planning and management at the area, since it is under direct influence of hydroeletric projects from the upper part of Madeira river (RO). It contains as basic economic activities for subsistence: agriculture and extensive livestock. To be possible, was used the method of landscape analysis developed by George Bertrand in 1972, which when analyzing the landscape, brought together several physical elements, besides other variables, such as the territory and geosystem. In order to quantify the geosystem and measure the watershed erosion, was used the Revised Universal Soil Loss Equation (RUSLE), from which estimated the annual loss of soil. Its advantage is the fact that it is a full modeling that, when using statistical parameters and mathematical equations, tends to ensure good accuracy in the results. The soil loss values due hydro erosion calculated for the refered watershed were 0.937 ton/ha year, ten times lower than the natural potential of soil loss, which indicated that the land use that was observed in this study is inadequate to the natural watershed system, whose projected future trend indicates strong scenario of